Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(A=4\cdot\dfrac{5}{2}\sqrt{x}-\dfrac{8}{3}\cdot\dfrac{3}{2}\sqrt{x}-\dfrac{4}{3x}\cdot\dfrac{3x}{8}\cdot\sqrt{x}\)
\(=10\sqrt{x}-4\sqrt{x}-\dfrac{1}{2}\sqrt{x}\)
\(=\dfrac{11}{2}\sqrt{x}\)
b: \(B=\dfrac{y}{2}+\dfrac{3}{4}\cdot\left|2y-1\right|-\dfrac{3}{2}\)
\(=\dfrac{y}{2}+\dfrac{3}{4}\left(1-2y\right)-\dfrac{3}{2}\)
=1/2y+3/4-3/2y-3/2
=-y-3/4
Ta có : \(B=\frac{y}{2}+\frac{3}{4}\sqrt{1-4y+4y^2}-\frac{3}{2}\)
=> \(B=\frac{2y-6}{4}+\frac{3}{4}\sqrt{\left(2y-1\right)^2}\)
=> \(B=\frac{\left(2y-6+3\sqrt{\left(2y-1\right)^2}\right)}{4}\)
=> \(B=\frac{\left(2y-6+3\left(1-2y\right)\right)}{4}\)
=> \(B=\frac{\left(2y-6+3-6y\right)}{4}=\frac{-4y-3}{4}=-\left(y+\frac{3}{4}\right)\)
\(\frac{y}{2}+\frac{3}{4}\sqrt{1-4y+4y^2}-\frac{3}{2}\)
\(=\frac{y}{2}+\frac{3}{4}\sqrt{\left(2y-1\right)^2}-\frac{3}{2}\)
\(=\frac{y}{2}+\frac{3}{4}\left|2y-1\right|-\frac{3}{2}\)(*)
Theo giả thiết \(y\le\frac{1}{2}\Leftrightarrow2y-1\le0\)
(*) \(=\frac{y}{2}+\frac{3}{4}\cdot\left(1-2y\right)-\frac{3}{2}\)
\(=\frac{y}{2}+\frac{3}{4}-\frac{3y}{2}-\frac{3}{2}\)
\(=\frac{-2y}{2}-\frac{3}{4}\)
\(=-y-\frac{3}{4}\)
\(\frac{2}{x-3}\sqrt{\frac{x^2-6x+9}{4y^4}}=\frac{2}{x-3}.\frac{\sqrt{x^2-6x+9}}{\sqrt{4y^4}}=\frac{2}{x-3}.\frac{\sqrt{\left(x-3\right)^2}}{\sqrt{\left(2y^2\right)^2}}\)
\(=\frac{2}{x-3}.\frac{x-3}{2y^2}=\frac{1}{y^2}\)
\(\frac{2}{x-3}\sqrt{\frac{x^2-6x+9}{4y^4}}\)
\(=\frac{2}{x-3}\sqrt{\frac{\left(x-3\right)^2}{\left(2y^2\right)^2}}\)
\(=\frac{2}{x-3}.\left|\frac{x-3}{2y^2}\right|\)
\(=\frac{2}{x-3}.\frac{3-x}{2y^2}\)( vi \(x< 3;y\ne0\))
\(=\frac{-2}{2y^2}\)
\(=\frac{-1}{y^2}\)
\(=\frac{\sqrt{y}}{\sqrt{y}-2}\times\frac{\left(\sqrt{y}-2\right)\left(\sqrt{y}+2\right)}{\sqrt{4}\cdot\sqrt{y}}+\frac{\sqrt{y}}{\sqrt{y}+2}\times\frac{\left(\sqrt{y}+2\right)\left(\sqrt{y}-2\right)}{\sqrt{4}\cdot\sqrt{y}}\)
\(=\frac{\sqrt{y}+2}{\sqrt{4}}+\frac{\sqrt{y}-2}{\sqrt{4}}=\frac{2\sqrt{y}}{2}=\sqrt{y}\)
b/ đkxd \(y>0;y\ne4\)
tại \(y=\frac{1}{4}\)( t/m dkxd ) nên \(P=\sqrt{y}=\sqrt{\frac{1}{4}}=\frac{1}{2}\)
Bài làm:
Ta có:
\(\frac{\sqrt{50x^4y^2}}{\sqrt{200x^2}y^4}=\frac{5x^2y\sqrt{2}}{10xy^4\sqrt{2}}=\frac{x}{2y^3}\)